A Democratic Leadership To Sustain The Success Of TQM: The Case Of A Sri Lankan Public Hospital - Kaluarachchi, K.A.S.P. (My University, 2011)
The purpose of this paper is to examine the research issue of how TQM implementation of an organization is accomplished within its cultural change. The issue is examined and discussed in relation to how Japanese 5-S based TQM implementation of a Sri Lankan public hospital was accomplished within its cultural change. By adopting the case study research strategy with multiple data gathering techniques and qualitative data analytical methods, the paper reveals that culture change process of the hospital has taken place through its 5-S based TQM activities implemented in 2003. It was that the democratic leadership type communication of the CEO of the hospital has initiated its culture change process with the TQM implementation. The hospital has won a national quality award in 2003 for its service performance improvement by practicing Japanese 5-S based TQM activities. However, the hospital has not continued its TQM success for a long period. This was because of the personal values of the CEO as a whole were not sufficient to maintain the ideal type/democratic type communication with different employee categories (i.e., divisional heads, doctors, nursing sisters and nurses, paramedical staff, midwifery staff, clerical staff, and support staff) them to engage in the TQM implementation with high integrity for a long period. Although the CEO’s personal values comprised both teamwork and openness values which enabled the integration of TQM activities within the hospital in short-term, the CEO lacked the responsiveness, forgiveness, practical orientation, and continuation values. Consequently, the CEO was not able to continue the culture change process of the hospital towards its TQM implementation for a long period. The paper also reveals that the national culture values of Sri Lanka considered for this study have constrained personal values of the CEO within the hospital context of TQM implementation.